Review. Flowers biology in apricot and its implications for breeding - Burgos, L.=700 1 Alburquerque, N.; Egea, J.
(Es, En)
ilus., 143 ref.
Keywords: ALBARICOQUE; POLINIZACION; HERENCIA GENETICA; ESTERILIDAD MASCULINA; GINECEO; AUTOCOMPATIBILIDAD; ESPAÑA; PERIODO DE POLINIZACION EFECTIVA